2020
DOI: 10.3390/ai1040032
|View full text |Cite
|
Sign up to set email alerts
|

Transfer-to-Transfer Learning Approach for Computer Aided Detection of COVID-19 in Chest Radiographs

Abstract: The coronavirus disease 2019 (COVID-19) global pandemic has severely impacted lives across the globe. Respiratory disorders in COVID-19 patients are caused by lung opacities similar to viral pneumonia. A Computer-Aided Detection (CAD) system for the detection of COVID-19 using chest radiographs would provide a second opinion for radiologists. For this research, we utilize publicly available datasets that have been marked by radiologists into two-classes (COVID-19 and non-COVID-19). We address the class imbalan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…As of 18 March 2021—a year after the WHO categorized the COVID-19 outbreak as a pandemic, there were 120,915,219 cumulative cases and 2,674,078 total deaths [ 1 ]. The number of infected cases is believed to be underreported because of asymptomatic infection, hesitancy to get tested, and lack of alternative testing procedures [ 2 , 3 , 4 , 5 ]. The pandemic disrupted many aspects of human activity, leading to worldwide economic challenges including increased unemployment, income, food, and housing insecurity, and intimate partner violence [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As of 18 March 2021—a year after the WHO categorized the COVID-19 outbreak as a pandemic, there were 120,915,219 cumulative cases and 2,674,078 total deaths [ 1 ]. The number of infected cases is believed to be underreported because of asymptomatic infection, hesitancy to get tested, and lack of alternative testing procedures [ 2 , 3 , 4 , 5 ]. The pandemic disrupted many aspects of human activity, leading to worldwide economic challenges including increased unemployment, income, food, and housing insecurity, and intimate partner violence [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A hybrid model combining CNN and Bi-LSTM was designed for COVID infection detection from CT scans [ 5 ]. Transfer learning based CAD system is built using chest radio graph images [ 36 ]. In contrast to traditional transfer learning, a deep transfer learning based approach was proposed to identify corona infection from chest X-ray images [ 31 ].…”
Section: Background Studymentioning
confidence: 99%
“…Currently, ML/DL has played a significant role in boosting many CAD systems' diagnostic efficiency for various medical applications such as diagnosing and detecting different pulmonary diseases. Recent studies have shown that DL techniques have proven to be very efficient for CAD systems in radiography [48]. Hence, C.T.…”
Section: Investigation On Classification Performancementioning
confidence: 99%